The larva of Hetaerina mendezi Jurzitza, with comments on H. rosea Selys (Zygoptera: Calopterygidae) - Von Ellenrieder, Natalia (2007)
H. mendezi larva is described and illustrated for the first time based on specimens from Misiones Province, Argentina. Larvae of H. rosea from NW Argentina are found to partially differ from its original larval description, and that species is re-diagnosed. A comparative table for all known larvae of Hetaerina and related calopterygid genera is provided.